Proteomic characterization of Corynebacterium pseudotuberculosis biofilm / Syaida Anati Abd Rashid - Abd Rashid, Syaida Anati (2023)
Corynebacterium pseudotuberculosis is a pathogenic intracellular parasite causing caseous lymphadenitis (CLA) mostly in sheep and goats, thus, leading to significant economic losses. The morphology, biochemical composition, and antimicrobial susceptibility pattern of C. pseudotuberculosis biofilm have previously been addressed. However, little is known about the whole-cell proteome expression in C. pseudotuberculosis biofilm. The present study was performed to determine proteome profiles of planktonic and biofilm fractions of C. pseudotuberculosis using 1D-SDSPAGE and to identify differentially expressed proteins during the biofilm formation by C. pseudotuberculosis using LC-MS/MS. The FESEM image showed that heterogenous C. pseudotuberculosis biofilm was successfully formed within 24h. The treatment with antimicrobials substantially inhibited the viability of the C. pseudotuberculosis biofilm. The percentage of biofilm inhibition was found to be in the range between 12.92% to 87.44%. Both planktonic and biofilm fractions showed the expression of nine protein bands ranging between 33.7 kDa and 150 kDa. However, a protein band of 48.3 kDa appeared in the planktonic fraction but not in the biofilm fraction.